2022
DOI: 10.3899/jrheum.221010
|View full text |Cite
|
Sign up to set email alerts
|

Improving Outcomes for Patients With Hemophagocytic Lymphohistiocytosis

Abstract: Hemophagocytic lymphohistiocytosis (HLH) is a rare syndrome of uncontrolled immune activation often triggered by genetic defects in the primary form, and also by infection, rheumatic diseases, and malignancy in the secondary form. It is characterized by fever, hyperferritinemia, cytopenias, hepatosplenomegaly, and multiorgan dysfunction.1,2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…In clinical trials, IRRs were observed in approximately 3% of those receiving crizanlizumab infusions. 5 In our experience, most IRRs respond quickly to medication, and supportive measures can be considered for subsequent infusions on a case-by-case basis. All patients reported improvements in quality of life due to the reduction in priapic events, which they attributed to crizanlizumab.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In clinical trials, IRRs were observed in approximately 3% of those receiving crizanlizumab infusions. 5 In our experience, most IRRs respond quickly to medication, and supportive measures can be considered for subsequent infusions on a case-by-case basis. All patients reported improvements in quality of life due to the reduction in priapic events, which they attributed to crizanlizumab.…”
Section: Discussionmentioning
confidence: 89%
“…Crizanlizumab is approved to reduce the frequency of VOCs in patients aged 16 years and older with SCD and is currently under investigation for the treatment of SCD-related priapism in the SPARTAN clinical trial (NCT03938454). 5,6 The SPARTAN trial is currently recruiting, with results expected in 2023. 6 Given the findings in these 3 patients, crizanlizumab shows promise as a potential agent in the management of SCD-related priapism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rousset and Ray for their comment 1 on our manuscript and for highlighting the importance of a consensus-driven, multidisciplinary approach to the management of patients with hemophagocytic lymphohistiocytosis (HLH) and macrophage activation syndrome (MAS). 2 As Rousset and Ray note, 1 the nature of MAS-HLH lends itself to the need for input from many subspecialties and a predetermined approach to the diagnosis and treatment of affected patients. The presentation of MAS-HLH can be pleomorphic, ranging from the classic presentation of multisystem dysfunction to organ-specific manifestations such as central nervous system (CNS)-isolated HLH.…”
Section: Dr Degar Et Al Replymentioning
confidence: 99%